2001
DOI: 10.1007/s004220100256
|View full text |Cite
|
Sign up to set email alerts
|

Noise-induced transition in excitable neuron models

Abstract: We studied the influence of noisy stimulation on the Hodgkin-Huxley neuron model. Rather than examining the noise-related variability of the discharge times of the model--as has been done previously--our study focused on the effect of noise on the stationary distributions of the membrane potential and gating variables of the model. We observed that a gradual increase in the noise intensity did not result in a gradual change of the distributions. Instead, we could identify a critical intermediate noise range in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…[47]). Similar behavior of the membrane-potential distribution has been reported in a HH neuron model [33] [28]. When adopting the Gaussian assumption, we may express the average of fluctuations in terms of the first and second moments only.…”
Section: Neuron Ensembles a Dmf Approximationsupporting
confidence: 70%
“…[47]). Similar behavior of the membrane-potential distribution has been reported in a HH neuron model [33] [28]. When adopting the Gaussian assumption, we may express the average of fluctuations in terms of the first and second moments only.…”
Section: Neuron Ensembles a Dmf Approximationsupporting
confidence: 70%
“…Thus noise can be used to reveal dynamical regimes of a system that are available but are hidden normally. There are several theoretical studies of noise-induced transitions in biological systems, including noise-induced transitions in Hodgkin-Huxley models of excitable membranes (Horsthemke and Lefever 1981;Tanabe and Pakdaman 2001), and noise-induced bursting in models of mammalian thermoreceptors (Huber et al 2000;Longtin and Hinzer 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations for a single FN neuron have shown that for weak noises, the distribution of x(t) of the membrane potential nearly obeys the Gaussian distribution, although for strong noises, the distribution of x(t) deviates from the Gaussian, taking a bimodal form [26] [27]. Similar behavior of the membrane-potential distribution has been reported also in the HH neuron model [28] [29]. We express Eqs.…”
Section: A Basic Formulationmentioning
confidence: 52%